Susceptibility to reinfection after a primary chlamydial genital infection - Roger G. Rank; Byron E. Batteiger; Lee S.F. Soderberg (1988)
Female guinea pigs which had been infected genitally with the agent of guinea pig inclusion conjunctivitis were challenged at various times after infection with fresh inocula to determine the duration of immunity resulting from the primary infection. At 30 days after infection, most guinea pigs were resistant to reinfection, as indicated by the inability to isolate chlamydiae from cervical swabs. However, at 77, 155, and 294 days, all animals became reinfected, although the course of the infection was abbreviated and of lower intensity. When various immune parameters were examined, a decrease in antibodies in both serum (immunoglobulin G [( IgG]) and genital secretions (IgA, IgG) was observed after 30 days. A decrease in antibodies to the major outer membrane protein and an 84K component was noted in serum. In genital secretions, IgA antibodies to all major chlamydial components declined markedly after 30 days. Cell-mediated immunity as measured by proliferation of peripheral blood lymphocytes to guinea pig inclusion conjunctivitis antigen also was at a peak response 30 days after infection and decreased thereafter. Thus, loss of complete immunity could not be associated with a particular immune parameter. When genital secretions were examined 14 days after the challenge infection, IgA antibody levels to the lipopolysaccharide and 61K protein components had increased in intensity, whereas other antibodies were relatively low. In addition, complete immunity to a third infection was not increased in duration when animals had recovered from two previous genital infections.